2021
DOI: 10.1155/2021/5561755
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Bagasse-Derived Activated Carbon- (AC-) Epoxy Vitrimer Biocomposite: Thermomechanical and Self-Healing Performance

Abstract: Vitrimeric materials have emerged as fascinating and sustainable materials owing to their malleability, reprocessability, and recyclability. Sustainable vitrimeric materials can be prepared by reinforcing polymeric matrix with bioderived fillers. In the current work, a sustainable vitrimer is prepared by incorporating biomass-derived activated carbon (AC) filler into the epoxy matrix to achieve enhanced thermal and mechanical properties. Thus, prepared biocomposite vitrimers demonstrate a lower-temperature sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Leaving an impression of interest, sustainable polymeric protective coatings have been in prime focus for corrosion inhibition of metallic surfaces and thus explored in this report. 6,42 Along with the inherent properties of vegetable oils, external materials/ groups can be easily coupled due to the presence of different functional moieties in oil, as required for different coating applications. [64][65][66] 2.…”
Section: Signicance and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaving an impression of interest, sustainable polymeric protective coatings have been in prime focus for corrosion inhibition of metallic surfaces and thus explored in this report. 6,42 Along with the inherent properties of vegetable oils, external materials/ groups can be easily coupled due to the presence of different functional moieties in oil, as required for different coating applications. [64][65][66] 2.…”
Section: Signicance and Backgroundmentioning
confidence: 99%
“…renewable substances like cellulose, starch, sugar, etc. [4][5][6] Vegetable oils are the centre of attention owing to their favourable chemical structure, availability, cost, and unsaturated sites for functional group fabrication, thus advantageous for designing the molecules from scratch. 78 A variety of vegetable oils, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For each material, the proper, different combination of treatments should be found and optimised. It can also provide the self-healing properties of the structure [ 27 ]. In some cases, animal sources are efficiently used.…”
Section: Natural Fibres As Sustainable Matrix Reinforcementsmentioning
confidence: 99%
“…Rana et al has reported a sustainable vitrimer, prepared by incorporating biomass-derived activated carbon (AC) filler into the epoxy matrix [ 81 ]. The epoxy vitrimer has been prepared in single step reaction with bisphenol A diglycidyl ether (BADGE) and 2- aminophenyl disulfide (2-AFD) at 80 °C for 15 min and then added a different percentage of activated carbon dispersed solution into that.…”
Section: Classification Of Bio-vitrimersmentioning
confidence: 99%
“…Healing efficiency of vitrimer was calculated via the stress-strain relationship for ( b ) EP-p and ( c ) EP-1. Reproduced with permission [ 81 ].…”
Section: Figurementioning
confidence: 99%